1999
DOI: 10.1093/hsw/24.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Risky Sex Behavior and Substance Use among Young Adults

Abstract: Many young adults, despite widespread prevention and education efforts that target this age group, engage in behaviors that place them at risk of HIV infection. These behaviors include frequent experimentation with alcohol and other drugs before sex, sexual activity with different partners, and inconsistent safe-sex practices. The combination of these risky behaviors causes increased concern about the spread of HIV among this age group. The study discussed in this article examined the relationship between subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
4
15

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 0 publications
10
66
4
15
Order By: Relevance
“…The positive relationship between alcohol intoxication and most sexual risk behaviors is consistent with those from the majority of previous studies conducted among adolescents, college students, and rural residents (Staton et al, 1999;Duncan et al, 1999). Likewise, the findings are consistent with some previous studies (Kingree and Betz, 2003) in western countries as well as a survey conducted among commercial sex workers in China, which reported 42% of sexual workers and 32% of their clients used alcohol during sex (Rogers et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The positive relationship between alcohol intoxication and most sexual risk behaviors is consistent with those from the majority of previous studies conducted among adolescents, college students, and rural residents (Staton et al, 1999;Duncan et al, 1999). Likewise, the findings are consistent with some previous studies (Kingree and Betz, 2003) in western countries as well as a survey conducted among commercial sex workers in China, which reported 42% of sexual workers and 32% of their clients used alcohol during sex (Rogers et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…Twenty-four percent of teens 15-17 years of age say that their alcohol and drug use led them to do more sexually than they had planned (CASA, 1999). Heavy use of alcohol was correlated with increased casual sex without condoms and with increased number of sexual partners among youth (Staton et al, 1999). Limited research conducted in developing countries in Asia and Africa also suggested a positive relationship between alcohol use and sexual risk behaviors.…”
Section: Introductionmentioning
confidence: 95%
“…Unger et al (1998) noted that early adolescent homeless youth may be at lower risk of acquiring HIV and may be more receptive to interventions that help them get off the streets compared to older youth. Some research suggests that risk behaviors increase with age because of increases in autonomy and freedom and from social control agents (Bachman et al 1997;Staton et al 1999). Older age in combination with homelessness may be associated with more opportunities to engage in high-risk activities.…”
Section: Age and Gendermentioning
confidence: 99%
“…Marijuana use is associated with criminal behavior, notably attempted homicide, drug trafficking, and delinquency in adolescents and young adults (Fergusson and Horwood, 1997;Friedman et al, 2001;Watts and Wright, 1990;White, 1991). Marijuana use has been associated with risky sexual behavior (Duncan et al, 1999;Kingree et al, 2000;Kingree and Betz, 2003;Staton et al, 1999) and chronic use may serve as a predictor for HIV risk (Malow et al, 2001). Marijuana is the most frequently used illicit drug implicated in intoxicated driving (Brookoff et al, 1994;Moskowitz, 1985;Walsh and Mann, 1999).…”
Section: Introductionmentioning
confidence: 99%